Spirit run eaudiobook A 6000-mile marathon through north america's stolen land. - Álvarez, Noé (HighBridge Audio, 2020)
Growing up in Yakima, Washington, Noe Álvarez worked at an apple-packing plant alongside his mother, who "slouched over a conveyor belt of fruit, shoulder to shoulder with mothers conditioned to believe this was all they could do with their lives." A university scholarship offered escape, but as a first-generation Latino college-goer, Álvarez struggled to fit in. At nineteen, he learned about a Native American/First Nations movement called the Peace and Dignity Journeys, epic marathons meant to renew cultural connections across North America. He dropped out of school and joined a group of Dene, Secwepemc, Gitxsan, Dakelh, Apache, Tohono O'odham, Seri, Purepecha, and Maya runners, all fleeing difficult beginnings. Telling their stories alongside his own, Álvarez writes about a four-month-long journey from Canada to Guatemala that pushed him to his limits. He writes not only of overcoming hunger, thirst, and fear-dangers included stone-throwing motorists and a mountain lion-but also of asserting Indigenous and working-class humanity in a capitalist society where oil extraction, deforestation, and substance abuse wreck communities.